Limits and Challenging Factors of the Dispute Settlement Mechanism in the Light of China- ASEAN Free Trade Agreement Perspective - Sookhakich, Pattawee (Asian Political Science Review, 2019)
The aim of this article is to understand the dispute settlement mechanism in the ASEANChina Free Trade Agreement, hereinafter ACFTA. The ACFTA consists of ten ASEAN members plus one, namely Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar (Burma), the Philippines, Singapore, Thailand, Vietnam and China. This article will present the current situation and motives behind China and the ASEAN’s Free Trade Area engagement. The ACFTA was signed in order to embrace the opportunities and face the challenges of being integrated into the region’s economy. One of the major limitations of ASEAN economic regulation, especially free trade regulation, is the ASEAN’s underdeveloped Dispute Settlement Mechanism (DSM). Interestingly, the number of cases that have arisen under the ACFTA is nil since its creation in 2005, which places the ACFTA DSM in doubt over its effectiveness. The legal problems regarding the China-ASEAN free trade area (FTA) will also be discussed in this article. Furthermore, this article focuses on what would be an appropriate DSM’s framework, and its legal issues concerning how the dispute settlement mechanism from the perspective of the ACFTA, should be developed in order to improve the China-ASEAN dispute resolution mechanism and facilitate legal research of countries in the region.